2023
DOI: 10.1021/acs.jafc.2c08731
|View full text |Cite
|
Sign up to set email alerts
|

Laminaria Japonica Polysaccharide Improved the Productivities and Systemic Health of Ducks by Mediating the Gut Microbiota and Metabolome

Anxin Liu,
Eunyoung Kim,
Jiamei Cui
et al.

Abstract: This study investigated the beneficial effects of a Laminaria japonica polysaccharide (LJPS) on the systemic health of ducks by modulating the gut microbiome and metabolome. Our findings demonstrated that the LJPS supplementation enhanced the overall growth performance and physiological immune and antioxidant index of ducks. In addition, the LJPS-fed group significantly increased abundances of intestinal Bacteroides and Prevotellaceae with decreased α-diversity than that in the control group. Among the total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The intestinal improvement effects of polysaccharides were closely related to their effects on intestinal flora [51,52]. The structure of fish intestinal microbes is affected by the environment and feed [53].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal improvement effects of polysaccharides were closely related to their effects on intestinal flora [51,52]. The structure of fish intestinal microbes is affected by the environment and feed [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of APGs has significant beneficial effects on growth performance and disease prevention in farmed animals, their use is partially restricted and prohibited worldwide due to the increasing problem of bacterial resistance. Studies have reported the beneficial effects of plant polyphenols, flavonoids and polysaccharides on livestock and poultry breeding have been studied and reported (46)(47)(48). The results showed that TMAE supplementation could increase the daily gain, improve the serum chemical index, enhance the antioxidant capacity of serum, liver and ileum, enhance the immune function of liver and intestine, and then improve the growth performance of broilers.…”
Section: Discussionmentioning
confidence: 99%